PERGESERAN NILAI-NILAI BUDAYA DALAM KOMUNIKASI PADA REMAJA JORONG MUNGKA TENGAH MENGGUNAKAN APLIKASI TIKTOK - Al Harist, M.Qadhafi; Lani, Oktri Permata (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The main problem in this essay is the shift in cultural values in communication among Jorong Mugka Tengah teenagers in using the TikTok application. The purpose of this research is to find out how cultural values are in communication among teenagers in Jorong Mungka Tengah and what are the shifting factors of cultural values in communication in teenagers in Jorong Mungka Tengah. The main problem in this essay is the shift in cultural values in communication among Jorong Mugka Tengah teenagers in using the TikTok application. The purpose of this research is to find out how cultural values are in communication among teenagers in Jorong Mungka Tengah and what are the shifting factors of cultural values in communication in teenagers in Jorong Mungka TengahThe type of research that the author conducted was qualitative method research . Based on research, it can be seen that the process of shifting cultural values occurs due to several forms and factors, namely the form of symbols, slogans and missions. Furthermore, communication among teenagers in Central Jorong Mungka changed after getting to know Tiktok because it was